Natural enemies of the South American moth, Tuta absoluta, in Europe, North Africa and Middle East, and their potential use in pest control strategies - Zappalà, Lucia; Biondi, Antonio; Alma, Alberto; Al-Jboory, Ibrahim J.; Arnò, Judit; Bayram, Ahmet; Chailleux, Anaïs; El-Arnaouty, Sayed A.; Gerling, Dan; Guenaoui, Yamina; Shaltiel-Harpaz, Liora; Siscaro, Gaetano; et al. (My University, 2013)
The South American tomato leafminer, Tuta absoluta Meyrick (Lepidoptera: Gelechiidae), is an invasive Neotropical pest. After its first detection in Europe, it rapidly invaded more than 30 Western Palaearctic countries becoming a serious agricultural threat to tomato production in both protected and open-field crops. Among the pest control tactics against exotic pests, biological control using indigenous natural enemies is one of the most promising. Here, available data on the Afro-Eurasian natural enemies of T. absoluta are compiled. Then, their potential for inclusion in sustainable pest control packages is discussed providing relevant examples. Collections were conducted in 12 countries, both in open-field and protected susceptible crops, as well as in wild flora and/or using infested sentinel plants. More than 70 arthropod species, 20 % predators and 80 % parasitoids, were recorded attacking the new pest so far. Among the recovered indigenous natural enemies, only few parasitoid species, namely, some eulophid and braconid wasps, and especially mirid predators, have promising potential to be included in effective and environmentally friendly management strategies for the pest in the newly invaded areas. Finally, a brief outlook of the future research and applications of indigenous T. absoluta biological control agents are provided.
Keywords: Biological control; Generalist predators; Integrated pest management; Invasive species; Parasitoid community; Western Palaearctic